2020
DOI: 10.3389/fphar.2020.01014
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic-Guided Algorithm to Improve Daily Dose of Warfarin in Elder Han-Chinese Population

Abstract: Objectives: To verify the accuracy of the International Warfarin Pharmacogenetics Consortium (IWPC) algorithm, identify the effects of genetic and clinical factors on warfarin stable dose, and to establish a new warfarin stable dose prediction algorithm for the elderly Han-Chinese population under the guidance of pharmacogenetics. Methods: According to the inclusion criteria, 544 non-valvular atrial fibrillation patients taking warfarin for anticoagulation treatment were enrolled. Data information of three gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
(39 reference statements)
1
9
0
Order By: Relevance
“…The estimated initial therapeutic dose of warfarin was 3.0 mg/day for the hypothetical patient, according to the algorithm based on clinical factors and the CYP2C9 and VKORC1 genotypes ( Gage et al, 2008 ). The mean stable dosage required for the elderly Chinese patients identified in Ren’s study ( Ren et al, 2020 ) were similar to the estimated initial dose shown above. However, this dose was far lower than the actual dosage of warfarin used for the patient possessing the I213V mutation.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The estimated initial therapeutic dose of warfarin was 3.0 mg/day for the hypothetical patient, according to the algorithm based on clinical factors and the CYP2C9 and VKORC1 genotypes ( Gage et al, 2008 ). The mean stable dosage required for the elderly Chinese patients identified in Ren’s study ( Ren et al, 2020 ) were similar to the estimated initial dose shown above. However, this dose was far lower than the actual dosage of warfarin used for the patient possessing the I213V mutation.…”
Section: Discussionsupporting
confidence: 73%
“…The mean stabilized warfarin dose for this population that was applied in the project ranged from 2.39 to 4.06 mg/day. We found that the CYP2C9 wild-type *1*1 and VKORC1 (AA) were most common group (275 cases, 76.39%); the mean stabilized dose of warfarin was 3.0 mg/day ( Ren et al, 2020 ). In addition, we used a prediction model ( www.warfarindosing.org ) to estimate the initial therapeutic dose of warfarin in a hypothetical patient possessing CYP2C9*1/*1 and VKORC1 A/A genotype.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Operational definitions (adapted from references). 7,8,11,12,14,15 Actual warfarin dose: is the maintenance dosing that is taken by the patient. 11,12,14 Warfarin 5 mg fixed standard dose: it is the strategy to initiate warfarin therapy by given 5 mg dose then after 3 days can be adjusted according to INR.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,11,12,14,15 Actual warfarin dose: is the maintenance dosing that is taken by the patient. 11,12,14 Warfarin 5 mg fixed standard dose: it is the strategy to initiate warfarin therapy by given 5 mg dose then after 3 days can be adjusted according to INR. The warfarin fixed dose was defined as the average daily dose of warfarin (mg/day, weekly dose/7 days) when the INR was in the target range (2.0 to 3.0) for at least 3 consecutives (at least 7 to 14 days) days after warfarin treatment.…”
Section: Discussionmentioning
confidence: 99%